COVID-19 IN NEWBORNS: OWN EXPERIENCE ON THE EXAMPLE OF CLINICAL CASES - Н. Друцул-Мельник; Л. Іванова; М. Гарас; І. Савка; С. Савка (Bukovynian State Medical University, 2023)
Introduction. Currently, there is controversial information regarding the epidemiologic characteristics and severity of COVID-19 in pregnant women and newborns. Most researchers report the same severity of disease in pregnant and non-pregnant women, and a milder course of disease in the neonatal period, with the possibility of critical illness in some infants. Ideas about the possibility of transmission of SARS-CoV-2 to a newborn have changed. Since intrauterine transmission of the novel coronavirus is currently considered rare, COVID-19 in newborns is usually associated with postnatal transmission of the virus. The aim of the work was to analyze the epidemiologic and clinical features of the COVID-19 in newborns based on the analysis of clinical cases. Material and methods. On 2020, at the beginning of the COVID-19 pandemic, 11 newborns were admitted to the infectious diseases departments of Chernivtsi Regional Children's Clinical Hospital, 9 children were referred from home by a family physician, and 2 children were transferred from maternity care facilities. Diagnosis was confirmed by PCR-RT detection of SARS-CoV-2 RNA in nasal/oropharyngeal swabs. The research was conducted in accordance with the principles of bioethics, the conclusion of the Commission on Biomedical Ethics of the Bukovinian State Medical University on the observance of moral and legal rules for conducting medical-scientific research, Protocol No. 6 dated March 16, 2023. The research was carried out within the framework of scientific and research activity of the Department of Pediatrics and Infectious Diseases of Children of the Bukovinian State Medical University "Modern epidemiological, clinical-paraclinical and diagnostic features of the most common inflammatory infectious and non-infectious diseases in children", state registration number: 0122U002208. Results. The analysis of the epidemiologic data allowed to identify an intrafamilial source of infection in all identified cases (in one case the source of infection could not be identified), in most cases it was the mother, in one case the source of infection was the father and the grandmother. In most families there are older siblings who could serve as a potential additional source of infection, but respiratory symptoms in siblings were identified in one third of the families. In the late neonatal period, cases of horizontal virus transmission were characterized by mild symptoms of upper respiratory tract infection as acute nasopharyngitis, one case - as a mixture with secretory diarrhea. COVID-19 in another child was accompanied by acute gastroenteritis and moderate dehydration. The clinical picture of coronavirus infection in the remaining third of cases was characterized by lower respiratory tract infection as acute tracheobronchitis, acute obstructive bronchitis and bronchiolitis. Two infants were transferred from the maternity hospital after delivery because of COVID-19 maternal symptoms and SARS-CoV-2 RNA detection in the infants' nasal/oropharyngeal swabs on the first day of life. These children were asymptomatic with no clinical or laboratory evidence of an infectious-inflammatory process during observation. Conclusions. The presence of an exclusively family source of infection can be considered an epidemiological feature of COVID-19 in the neonatal period. In the case of horizontal transmission of the SARS-CoV-2 virus in newborns, the disease COVID-19 in most cases proceeds as mild upper respiratory tract infection, less often - as lower respiratory tract infection and/or secretory diarrhea. In the case of maternal COVID-19 disease before childbirth the vertical and/or antenatal infection mode and the subsequent asymptomatic neonatal COVID-19 cannot be denied.